Kontribusi Cara Belajar Dan Media Pembelajaran Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Penggunaan Alat Ukur Elektronika Kelas X Teknik Audio Video Di SMK Negeri 1 Kecamatan Guguak Kabupaten 50 Kota - Miswardi Miswardi; Sukaya Sukaya; Yusri Abdul Hamid (Universitas Negeri Padang, 2014)
This research is purposed to reveal the contribution of learning and instructional media on learning outcomes in subjects use electronic measuring instrument class X Audio Video Techniques In SMK Negeri 1 Kecamatan Guguak Kabupaten 50 Kota . The research is a descriptive correlational . The research population numbered is 59 people and sample totaled 37 students of class X Audio Video Techniques In SMK Negeri 1 Kecamatan Guguak Kabupaten 50 Kota Academic Year 2012/2013 .Using Technique of random sampling ( Simple random sampling ) . and Data collection using questionnaires and documentation . Data were analyzed using Pearson product moment correlation and multiple correlation for analysis . The results of data analysis showed : 1 ) how to learn to contribute 19.82 % of the student learning outcomes , 2 ) Learning Media contributed 25.16 % to the student learning outcomes , 3 ) How to Learn and Learning Media jointly contributed 27.84 % of the student learning outcomes in subjects Use of Electronic Measurement Techniques class X Audio Video SMK Negeri 1 Kecamatan Guguak Kabupaten 50 Kota . The results of this study indicate that the learning and instructional media contribute to student learning outcomes .